Complete and partial repair of massive rotator cuff tears provide sustainable long term improvement in clinical scores. (26th February 2021) - Besnard, Marion; Freychet, Benjamin; Clechet, Julien; Carrillon, Yannick; Godenèche, Arnaud
Objectives: The aim was to report results of arthroscopic repair of 86 massive cuff tears and decided to assess whether or not clinical scores were maintained 5 years later. Methods: Of the initial series of 86 shoulders, 2 patients died, 16 were lost to follow-up and 4 had a repeat surgery. Therefore, it was possible to reevaluate 64 patients. Repairs were complete in 44 cases and partial in 20 cases. Seventeen shoulders were pseudoparalytic. Tears with fatty degeneration at stage 4 or higher according to the Goutallier classification were not eligible for repair. Preoperatively, the Constant Score (CS), shoulder strength, location of the tear, tendon retraction and degree of fatty infiltration were assessed. Patients were assessed at 8.1±0.6 years [7.1-9.3] using absolute and age- and sex-adjusted CS, the subjective shoulder value (SSV) and the simple shoulder test (SST). Results: The absolute CS was 80.0±11.7 at the first follow-up (at 2-5 years) and decreased to 76.7±10.2 at the last follow-up (at 7-10 years) (p<0.001). The adjusted CS was 99.7±15.9 at the first follow-up and remained at 98.8±15.9 at the last follow-up (ns.). In terms of the other criteria, strength decreased over time (p<0.001) but pain, SSV and SST remained the same. Partial repairs had less strength at the first and last follow-up (p<0.05). Pseudoparalytic shoulders had a lower absolute and adjusted CS at the last follow-up (p<0.05) but the improvement in CS was greater (p=0.014). Conclusion: Partial and complete arthroscopic repair provide good long-term results in patients with massive rotator cuff tears, regardless of the location of the tear, the degree of fat infiltration (I to III according to the Goutallier classification) and even in case of a pseudoparalytic shoulder.